Normal and Delayed Fracture Healing: Symphony and Cacophony - Jha, S.; Blau, J. E.; Bhattacharyya, T. (Hormone and Metabolic Research, 2016)
The incidence of any fracture in the US is estimated to be 2 704 fractures per 100,000 person-years. Approximately 10 percent of these fractures develop complications of healing. The processes that occur during fracture healing mimic the processes that take place in the growth plate during development. The study of fracture healing represents a window to enhance our understanding of the processes of growth and development of bones and its reparative biology. This review is aimed for clinicians evaluating non-unions as an overview of different factors that inhibit fracture healing.
Keywords: skeletal injury; bone repair; callus formation